2020
DOI: 10.3892/ol.2020.11686
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA‑100 functions as a tumor suppressor in cervical cancer via downregulating the SATB1 expression and regulating AKT/mTOR signaling pathway and epithelial‑to‑mesenchymal transition

Abstract: Cervical cancer (CC) is a common malignant tumor among women worldwide, remaining the fourth most frequent cause of cancer death in women. Currently, microRNA (miRNA) is a prevalent topic in tumor-related research. The present study focused on the mechanisms of miR-100 in CC progression. qRT-PCR analysis revealed that the miR-100 expression was notably decreased in CC tissues. In addition, miR-100 downregulation was confirmed to be significantly related to the malignant clinicopathologic features of CC patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…SATB1 (a matrix protein binding nuclear matrix) is an oncogenic driver in most of carcinomas (including head and neck squamous cell carcinoma, nasopharyngeal carcinoma, and lung adenocarcinoma) [ 23 27 ]. Its role in ICC is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…SATB1 (a matrix protein binding nuclear matrix) is an oncogenic driver in most of carcinomas (including head and neck squamous cell carcinoma, nasopharyngeal carcinoma, and lung adenocarcinoma) [ 23 27 ]. Its role in ICC is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Aberrant expression of SATB1 has also been reported to be relevant to several human cancers. 19 , 20 Here, we aimed to validate the possible interaction between FOXA1 and SATB1, and to explore their functions in DN progression using a mouse model with DN and high glucose (HG)-treated podocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that miRNA-100 is associated with the adaptive immune system ( Negi et al, 2015 ), anti-inflammatory function in the vascular system ( Pankratz et al, 2018 ), and the occurrence, development, and cancer invasion ( Liu et al, 2012 ; Huang et al, 2020 ). Genetic variation in miRNA-100 rs1834306 was found to be an increased risk of gastrointestinal disease ( Zhu et al, 2020 ), increased risk of Hepatitis B virus ( Motawi et al, 2019 , 1834306), and a decreased risk for esophageal squamous cell carcinoma ( Zhu et al, 2015 ) in several studies.…”
Section: Discussionmentioning
confidence: 99%